2016
DOI: 10.1093/pcp/pcw064
|View full text |Cite
|
Sign up to set email alerts
|

Identification, and Functional and Expression Analyses of the CorA/MRS2/MGT-Type Magnesium Transporter Family in Maize

Abstract: Magnesium (Mg(2+)) is an essential macronutrient for plant growth and development, and the CorA/MRS2/MGT-type Mg(2+) transporters play important roles in maintaining Mg(2+) homeostasis in plants. Although the MRS2/MGT genes have been identified in two model plant species, Arabidopsis and rice, a comprehensive analysis of the MRS2/MGT gene family in other plants is lacking. In this work, 12 putative MRS2/MGT genes (ZmMGT1- ZmMGT12) were identified in maize and all of them were classified into five distinct subf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 59 publications
2
60
2
Order By: Relevance
“…Plants acquire magnesium needed for growth and development from the environment and distribute within the plants in the ionic form via Mg 2+ - permeable transporters [ 67 ]. The Mg 2+ transporters mediate Mg 2+ uptake, translocation, and sequestration into cellular storage compartments [ 68 , 69 ]. Furthermore, the gene model GRMZM2G085113 ( qgy-3 ) associated with grain yield under Striga infestation encodes the terminal ear1 protein, te1.…”
Section: Discussionmentioning
confidence: 99%
“…Plants acquire magnesium needed for growth and development from the environment and distribute within the plants in the ionic form via Mg 2+ - permeable transporters [ 67 ]. The Mg 2+ transporters mediate Mg 2+ uptake, translocation, and sequestration into cellular storage compartments [ 68 , 69 ]. Furthermore, the gene model GRMZM2G085113 ( qgy-3 ) associated with grain yield under Striga infestation encodes the terminal ear1 protein, te1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms for Mg transport and homeostasis in plant cells remain largely unknown. Genomes of many plants such as Arabidopsis , rice, and maize, encode homologs of the bacterial CorA-type proteins referred to as MGTs/MRS2s ( Li et al, 2001 , 2016 ; Saito et al, 2013 ). Some members of the MGT family have been functionally characterized, but the physiological roles of these transporters are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one mutation in Arabidopsis ( pam71 ) has been identified that influences Mn 2+ uptake into chloroplasts (Schneider et al ) and only one Mg 2+ transporter/channel has been identified in the chloroplast envelope membrane (MRS2‐11) (Finazzi et al ). A vacuolar Mn 2+ transporter MTP8 enhances tolerance and accumulation of Mn 2+ in rice (Chen et al ), and several plasma membrane members of the CorA/MRS2/MGT type Mg 2+ transporters seem to play roles in maintaining Mg 2+ homeostasis in Arabidopsis , rice, and maize (Li et al ). Certainly, cellular regulation of Mn 2+ and Mg 2+ activities warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%